2014
DOI: 10.1074/jbc.m113.527424
|View full text |Cite
|
Sign up to set email alerts
|

Poly(ADP-ribose) Polymerase 1 (PARP1) Associates with E3 Ubiquitin-Protein Ligase UHRF1 and Modulates UHRF1 Biological Functions

Abstract: Background: PARP1 and UHRF1 participate in heterochromatin dynamics and the maintenance of DNA methylation, raising the question of whether both proteins cooperate in these events. Results: We reveal a physical and functional poly(ADP-ribose)-mediated interaction of PARP1 with UHRF1 that helps to adjust UHRF1-regulated biological activities. Conclusion: PARP1 is a regulator of UHRF1-controlled H4K20me3 accumulation and DNMT1 expression. Significance: PARP1 associates and cooperates with UHRF1 to regulate heter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
37
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(39 citation statements)
references
References 58 publications
2
37
0
Order By: Relevance
“…The PARP1-EZH2 axis controls genes involved in cell differentiation; however, our data identify many additional pathways that are regulated by PARP activity, including genes that respond to different insults, such as DNA damage and oxidative stress, and genes involved in the ubiquitination pathway (27,48,49). Although works have shown that PARP is an important mediator in these pathways, our data extend the known contributions of PARP activity to include transcriptional regulation of multiple genes within these pathways, opening an interesting area of research.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…The PARP1-EZH2 axis controls genes involved in cell differentiation; however, our data identify many additional pathways that are regulated by PARP activity, including genes that respond to different insults, such as DNA damage and oxidative stress, and genes involved in the ubiquitination pathway (27,48,49). Although works have shown that PARP is an important mediator in these pathways, our data extend the known contributions of PARP activity to include transcriptional regulation of multiple genes within these pathways, opening an interesting area of research.…”
Section: Discussionmentioning
confidence: 98%
“…While PARP activity is important for the transcriptional regulation of pathways common to all cell types, including the stress response (27) and the ubiquitination pathway (49), this study extends the relationship between PARP activity and cellular functions to include the regulation of B cells. For example, gene ontology analysis of our RNA-seq data showed that PARP inhibition affects genes involved in the Nur77 and nuclear factor of activated T cell signaling pathways, which are activated by B cell receptor stimulation (50,51).…”
Section: Discussionmentioning
confidence: 99%
“…The ubiquitin transferase, UHRF1, interacts with and recruits DNMT1 (Sharif et al 2007); thus, it could be repelled because it complexes with DNMT1. PARP1 can also be part of a complex with UHRF1 and DNMT1 (Sharif et al 2007), and it regulates UHRF1's interaction with DNMT1 by addition of poly(ADP-ribose) (De Vos et al 2014). In addition, PARP1 binds gene promoters and regulates transcription (Krishnakumar et al 2008).…”
Section: Resultsmentioning
confidence: 99%
“…Uhrf1 also possesses a RING finger domain, which has been linked to histone and protein ubiquitination and turnover (Citterio et al 2004;Liu et al 2013;Nishiyama et al 2013;Qin et al 2015). Moreover, Uhrf1 has also been involved in establishing and reorganizing heterochromatin sites (Papait et al 2008;De Vos et al 2014). In embryonic or skin stem cells, Uhrf1 is expressed during proliferation and downregulated upon differentiation (Sharif et al 2007;Sen et al 2010).…”
mentioning
confidence: 99%